2012
DOI: 10.1371/journal.pone.0041928
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Circulation Has Increased T-Cell Immunity during Childhood More than a Second Acellular Booster Vaccination in Dutch Children 9 Years of Age

Abstract: Here we report the first evaluation of T-cell responses upon a second acellular pertussis booster vaccination in Dutch children at 9 years of age, 5 years after a preschool booster vaccination. Blood samples of children 9 years of age were studied longitudinally until 1 year after the second aP booster and compared with those after the first aP booster in children 4 and 6 years of age from a cross-sectional study. After stimulation with pertussis-vaccine antigens, Th1, Th2 and Th17 cytokine responses were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…We have indications that booster responses induced by vaccination in combination with natural boosting with pertussis have resulted in increased T-cell responses in wP-primed children 6 and 9 years of age (39,40). In that study, however, the numbers of possible undiagnosed cases on the basis of elevated PT antibody levels were similar for wP-primed and aP-primed children.…”
Section: Discussionmentioning
confidence: 83%
“…We have indications that booster responses induced by vaccination in combination with natural boosting with pertussis have resulted in increased T-cell responses in wP-primed children 6 and 9 years of age (39,40). In that study, however, the numbers of possible undiagnosed cases on the basis of elevated PT antibody levels were similar for wP-primed and aP-primed children.…”
Section: Discussionmentioning
confidence: 83%
“…However, a previous study from the same group found Th1 and Th2 but no significant Th17 responses in C3H/HeJ and C3H/HeN mouse strains vaccinated with an aP containing PT and FHA (41). Nevertheless, data from two clinical studies recently showed negligible Th17 recall responses (∼10 pg/mL) in PBMC isolated from aP-vaccinated 4-y-old children before and after booster, suggesting aP does not induce Th17 memory in humans (43,44). Taken as a whole, the data presented in this study suggest that antibodies induced by aP vaccination are sufficient for preventing severe pertussis symptoms but do not mitigate colonization.…”
Section: Discussionmentioning
confidence: 96%
“…We earlier have demonstrated that wP-primed children 9 years of age showed higher numbers of pertussis-specific T EM than wP-primed children 4 years of age due to the preschool booster vaccination in combination with the high circulation of pertussis (25). So, specific T cells are able to differentiate further upon pertussis vaccination and infection.…”
Section: Stimulated Cd8mentioning
confidence: 97%